Multiomics profiling of human plasma and cerebrospinal fluid reveals ATN‐derived networks and highlights causal links in Alzheimer's disease - Shi, Liu; Xu, Jin; Green, Rebecca; Wretlind, Asger; Homann, Jan; Buckley, Noel J.; Tijms, Betty M.; Vos, Stephanie J. B.; Lill, Christina M.; Kate, Mara ten; Engelborghs, Sebastiaan; Sleegers, Kristel; et al. (Alzheimer's & dementia, 2023)
Introduction This study employed an integrative system and causal inference approach to explore molecular signatures in blood and CSF, the amyloid/tau/neurodegeneration [AT(N)] framework, mild cognitive impairment (MCI) conversion to Alzheimer's disease (AD), and genetic risk for AD. Methods Using the European Medical Information Framework (EMIF)‐AD cohort, we measured 696 proteins in cerebrospinal fluid (n = 371), 4001 proteins in plasma (n = 972), 611 metabolites in plasma (n = 696), and genotyped whole‐blood (7,778,465 autosomal single nucleotide epolymorphisms, n = 936). We investigated associations: molecular modules to AT(N), module hubs with AD Polygenic Risk scores and APOE4 genotypes, molecular hubs to MCI conversion and probed for causality with AD using Mendelian randomization (MR). Results AT(N) framework associated with protein and lipid hubs. In plasma, Proprotein Convertase Subtilisin/Kexin Type 7 showed evidence for causal associations with AD. AD was causally associated with Reticulocalbin 2 and sphingomyelins, an association driven by the APOE isoform. Discussion This study reveals multi‐omics networks associated with AT(N) and causal AD molecular candidates.